Monitoring load, recovery, and performance in young elite soccer players - Brink, M. S.; Nederhof, E.; Visscher, C.; Schmikli, S. L.; Lemmink, K. A. P. M. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to investigate the relation between training load, recovery, and monthly field test performance in young elite soccer players to develop training guidelines to enhance performance. In a prospective, nonexperimental cohort design, 18 young elite soccer players registered training and match duration for a full competitive season by means of daily training logs. Furthermore, session rating of perceived exertion (RPE) and total quality of recovery (TQR) scores were recorded. Weekly duration (TLd), load (duration × session RPE = TLrpe), and TQR scores were calculated for 1 and 2 weeks before a monthly submaximal interval shuttle run tests to determine interval endurance capacity. Participants spent on average 394.4 ± 134.9 minutes per week on training and game play with an average session RPE of 14.4 ± 1.2 (somewhat hard) and TQR of 14.7 ± 1.3 (good recovery). Random intercept models showed that every extra hour training or game play resulted in enhanced field test performance (p < 0.05). Session RPE and TQR scores did not contribute to the prediction of performance. The duration of training and game play in the week before field test performance is most strongly related to interval endurance capacity. Therefore, coaches should focus on training duration to improve interval endurance capacity in elite soccer players. To evaluate the group and individual training response, field tests should be frequently executed and be incorporated in the training program.